2021
DOI: 10.1002/slct.202103098
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenyl‐Based Aggregation‐Induced Emission Luminogen for Highly Sensitive and Selective Detection of 2,4,6‐Trinitrotoluene in Water

Abstract: Trace detection of nitroaromatic explosives in aqueous solution is important for environmental pollution evaluation and terrorist prevention. Here, a new pyrenyl‐based aggregation‐induced emission (AIE) fluorochrome (CPPyV) with desirable fluorescent performance was synthesized and applied to detect 2,4,6‐trinitrotoluene (TNT) in water. The fluorescence of CPPyV can be selectivity and efficiently quenched by TNT. The Stern‐Volmer constant (KSV) of CPPyV for TNT was determined to be 6.2×105 M−1, with a low dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Hao et al reported a new pyrene-based AIE chromophore 2 which can be used as a sensor for nitroaromatic compounds in water since nitroaromatic explosives are used in the manufacture of explosive devices [50,51]. The developed probe 2 had a large, conjugated skeleton of pyrene moieties, which contributed to the appearance of fluorescence.…”
Section: Recent Aie Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hao et al reported a new pyrene-based AIE chromophore 2 which can be used as a sensor for nitroaromatic compounds in water since nitroaromatic explosives are used in the manufacture of explosive devices [50,51]. The developed probe 2 had a large, conjugated skeleton of pyrene moieties, which contributed to the appearance of fluorescence.…”
Section: Recent Aie Materialsmentioning
confidence: 99%
“…When the concentration of TNT was higher than 1 × 10 −8 M, considerable fluorescence quenching was detected. These findings showed that cheap probe sensors might be employed for real‐time field and visual TNT detection (Figure 2) [51].…”
Section: Recent Aie Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical chemosensors relying on visible/fluorescence change upon TNT interaction offer a desirable alternative, mainly due to their low operational/instrumental requirements, ease of on-site applications, high sensitivity, and selectivity . Various types of fluorescent materials, such as small fluorophores, supramolecular systems, conjugated polymers, bioinspired materials, and aggregation-induced emission-active materials (AIEgens), have been used for the selective sensing of TNT. …”
Section: Introductionmentioning
confidence: 99%
“…In TFC AIEgens the variation of PL behaviour is caused by a thermal treatment inducing a molecular rearrangement [17,27,28]. Both MFC and TFC AIEgens have been used for advanced applications such as display devices, sensing, and optical data storage [17,24,[29][30][31][32][33][34][35][36][37][38]. Obviously, the structure-responsiveness relationship is critical for the prediction and understanding of AIEgens' fluorochromic response.…”
Section: Introductionmentioning
confidence: 99%